The legal protection of domain names in Jordanian legislation and the rules of the unified domain name dispute resolution policy issued by ICANN - AL-Khalaileh, Lana; Al-Billeh, Tareq; Manasra, Majd (Universitas Ahmad Dahlan, 2024)
Introduction to The Problem: The problem of the study was that the Jordanian legislative system is devoid of any special legal regulation or even a system that defines domain names in terms of their nature and means of legal protection for them. There is only the “Registration Policy” that the Ministry of Digital Economy and Entrepreneurship is implementing to register national domain names. This policy only addresses the technical and procedural aspect of domain name registration without specifying its legal nature.Purpose/Objective Study: The purpose of the study is to illustrate the topic's uniqueness and theoretical and practical significance. Due to the lack of specific regulations in many countries and the rise of cases handled by courts in this area, it presents several practical and legal issues. Therefore, the study aims to shed light on this phenomenon and try to find the best solutions to it in light of Jordanian legislation and the rules of the Unified Policy for Resolving Domain Name Disputes issued by ICANN.Design/Methodology/Approach: In its preparation, the study relies on the descriptive and analytical approach by describing the case, citing relevant legal texts, analyzing them, and applying them to reality. This is done by analyzing the texts of the Jordanian national domain name registration policy and comparing it with the legal texts contained in the rules of the Unified Policy for Resolving Domain Name Disputes issued by the ICANN under study.Findings: The study recommended a number of recommendations, the most important of which is the need to enact legislation specific to national domain names to determine the nature of these names and their legal nature. This legislation also includes provisions for their legal protection, stipulating appropriate legal ways and means to confront the assault on them, and provisions for liability resulting from them.Paper Type: Research Article